The role of state and creation of a market economy in Russia - Vladimir Mau (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
This paper examines the role of institutions in economic growth and the role of the institutions created by the Russian state in particular. The author stresses the finding that growth-supporting institutions vary according to the level of economic development in a country. In a post-industrial society, that Russia aspires to be, further economic development requires promotion of institutions securing e.g. property rights and economic freedom. Finally, based on these observations, the three development scenarios frequently discussed in the current Russian economic policy debates are analysed.
URN:NBN:fi:bof-201408072173
Keywords: 330